Establishment of Echinococcus granulosus EgM123 Recombinant Gene Rabies Virus SRV9 and Identification of Its Biological Characteristics - Yueqi Yang; Mengdan Hou; Guicheng Su; Xiaoyan Ma; Xiaohui Su; Kunlei Li; Songhan Liu; Luheng Xiao; Jingjing Yao; Jiahao Zhai; Xiaoying Wei; Yang Zhou; et al. (Viruses)
Canids act as a crucial intermediary in the transmission of rabies and Echinococcus granulosus, serving as co-infection hosts and pathogen carriers for both rabies and hydatid disease (HD) transmitted from animals to humans. Therefore, an effective and efficient bivalent oral vaccine for preventing HD and rabies is urgently required to reduce economic losses in husbandry resulting from rabies and HD. In this study, a full-length plasmid (pcDNA4-NPM+GΔCD+EgM123+eGFP+L) carrying the Echinococcus granulosus EgM123 gene and fluorescence reporter genes of eGFP and four auxiliary transfection plasmids of rabies virus SRV9 (pcDNA4-N, pcDNA4-P, pcDNA4-G, pcDNA-L) were established by reverse genetics approaches and co-transfected to BSR cells by electrotransfection. The co-transfected BSR cells showed green fluorescence 48 h after electrotransfection. The recombinant virus was exposed to the sixth-generation blind passage, with the N, P, G, and EgM123 genes amplified via RT-PCR, yielding targeted strips. The rescued virus-infected BSR cells were characterized by TEM, and the results indicated that bullet-like viral particles with an average size of 148.47 nm and a cyst structure were present in the cytoplasm of BSR cells; the expression levels of continuously cultivated 9th-, 10th-, 11th-, 12th-, and 13th-generation viruses were quantified by qRT-PCR, and the results showed that mRNA expression of the virus was upregulated. The LD50 titer of suckling rats was measured to be 10−1.4. The synthesized EgM123 recombinant gene rabies virus SRV9 can function as a vaccine strain for the development of the “Rabies-HD bivalent recombinant gene oral vaccine”, therefore aiding in the prevention and management of rabies and HD in animals.